INTERCONNECTION OF CONTRACTS: A STUDY ON THE SALE AND MAINTENANCE OF SACRIFICIAL COWS IN NAGARI SUMANI, SOLOK REGENCY (CASE STUDY OF MAK UJANG'S SACRIFICIAL COW MARKET) - Muhammad Latif Taftazani; Zainuddin Zainuddin (UIN Mahmud Yunus Batusangkar, 2024)
The aim of this research is to determine the form of buying and selling (bai), the form of ijarah, and the form of wadiah that occurs in the practice of buying and selling and caring for sacrificial cows carried out by the sacrificial cow seller